Implementasi Program Tarjim dalam Meningkatkan Prestasi Belajar Siswa Pada Mata Pelajaran Al Quran Hadits Di MTs Safinda Surabaya - Anik Khusnul Khotimah; Salucha; Lu'luatu Jauharatil Millah (Jurnal Keislaman, 2023)
The research aims to analyze the implementation of the Tarjim program in improving student learning achievement in the subjects of Quran and Hadith at MTS Safinda Surabaya. This type of research is field research using qualitative methods. The results of this research show that the implementation process of the Tarjim program at MTS Safinda consists of three stages: Planning, Implementation and Evaluation. In the planning stage, teachers, along with Quran and Hadith teachers, design lesson plans, set learning objectives, and determine materials, teaching media, and time allocation. Implementation involves dividing the class into small groups, where students take turns interpreting words in the verses and discussing their meanings. Evaluation is carried out through teacher reflection, written and oral tests, and grading students who can translate and understand the content of the Quranic verses. This program enhances students' learning achievement in Quran and Hadits by creating active and collaborative learning environments. The Tarjim approach aids material comprehension through interactive questioning and translation, facilitates students' memory retention, and enhances their interest in Quran and Hadith studies.